Proverbs in marriage: Counselling role and implications - Charles Owu-Ewie (Legon Journal of the Humanities, 2019)
The Akans of Ghana perceive marriage as an important ritual and an aspect of their socio-cultural life. Because of the importance attached to marriage and due to the fact that it is a preserve for the matured in society, the language used for its contraction is sophisticated and infused with proverbs. In recent times, the role of proverbs as a marriage-counselling tool has been overlooked in contemporary counselling. This paper, from a Pragmatic and Relevance Theory (RT) perspective, looked at the counselling role Akan proverbs play in marriage contraction. This descriptive qualitative study purposively selected proverbs in three episodes in different contexts of marriage contraction to see how they were used as counselling tools. The analysis of the data indicated that proverbs play a major counselling role in marriage. The counselling roles concentrated on themes like patience, co-operation, respect, sex, self-denial, hard work, faithfulness, loyalty, humility, child bearing and caring, and love. The implication is that contemporary professional marriage counsellors and priests should employ proverbs in their counselling sessions because proverbs portray what the Akan cherish as their worldview and an embodiment of their soul. This will ensure a clear understanding of the complexities of marriage.